2018
DOI: 10.1213/ane.0000000000002693
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Preoperative High-Dose Methylprednisolone on Postoperative Pain at Rest After Laparoscopic Appendectomy

Abstract: A 125-mg dose of methylprednisolone given intravenously 30 minutes before laparoscopic surgery for appendicitis seemed no better than placebo at providing a clinical meaningful reduction in postoperative pain at rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The reduction in postoperative hospital stay during the transition from open to laparoscopic appendectomy was to be expected as laparoscopic appendectomy has been shown to reduce postoperative stay when compared to open appendectomies (2). The median postoperative stay during the end of the study period corresponds well with the median postoperative stay reported in clinical trials on adult patients undergoing surgery for appendicitis during the same period in Denmark (17)(18)(19).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The reduction in postoperative hospital stay during the transition from open to laparoscopic appendectomy was to be expected as laparoscopic appendectomy has been shown to reduce postoperative stay when compared to open appendectomies (2). The median postoperative stay during the end of the study period corresponds well with the median postoperative stay reported in clinical trials on adult patients undergoing surgery for appendicitis during the same period in Denmark (17)(18)(19).…”
Section: Discussionsupporting
confidence: 58%
“…2 The median postoperative stay during the end of the study period corresponds well with the median postoperative stay reported in clinical trials on adult patients undergoing surgery for appendicitis during the same period in Denmark. [17][18][19] The reduced mortality was mostly driven by a reduced mortality for complicated cases and for elder patients. The increased use of minimal invasive surgery during the study period seems to have benefited the more fragile patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis evaluation, it was stated that peri-operative single-dose glucocorticoid administration reduced the incidence of PONV in large abdominal operations [8]. Despite the results of this study, in a similar study conducted in laparoscopic appendectomy patients, it was suggested that pre-operative administration of8 mg dexamethasone did not produce a reduction in the incidence of PONV, and pre-operative dexamethasone administration was not recommended for the prevention of PONV [14]. In another study conducted in orthopedic surgery patients, 125 mg MP was administered pre-operatively, and it was found to lead to a reduction in PONV.…”
Section: Discussionmentioning
confidence: 63%
“…In another study addressing this issue, the postoperative comfort in patients who had received pre-operative MP was evaluated using a questionnaire. Parameters, such as sleep quality, PONV, unaided mobilization, and fatigue were questioned in the questionnaire, and it was revealed that preoperative MP administration did not increase patient satisfaction [14]. Preventing nausea and vomiting after surgery and reducing pain are important for patient comfort.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences in pain scores or opioid consumption during admission. Studies of other procedures have shown conflicting results on the analgesic effects of GCs, with some reporting a reduction in postoperative pain scores 25–27 , and others no difference between groups 28–30 . Apart from explaining the different conclusions in terms of small study populations, differences in doses, outcome measures, and statistical analyses, there are most likely also procedure-specific differences in the magnitude of the inflammatory response and the mechanisms of pain.…”
Section: Discussionmentioning
confidence: 99%